Retinal arteriolar geometry is associated with cerebral white matter hyperintensities on magnetic resonance imaging - Doubal, Fergus N (Blackwell Publishing Ltd, 2010)
BACKGROUND: Cerebral small vessel disease (lacunar stroke and cerebral white matter hyperintensities) is caused by vessel abnormalities of unknown aetiology. Retinal vessels show developmental and pathophysiological similarities to cerebral small vessels and microvessel geometry may influence vascular efficiency. HYPOTHESIS: Retinal arteriolar branching angles or coefficients (the ratio of the sum of the cross-sectional areas of the two daughter vessels to the cross-sectional area of the parent vessel at an arteriolar bifurcation) may be associated with cerebral small vessel disease. METHODS: We performed a cross-sectional observational study in a UK tertiary referral hospital. An experienced stroke physician recruited consecutive patients presenting with lacunar ischaemic stroke with a control group consisting of patients with minor cortical ischaemic stroke. We performed brain magnetic resonance imaging to assess the recent infarct and periventricular and deep white matter hyperintensities. We subtyped stroke with clinical and radiological findings. We took digital retinal photographs to assess retinal arteriolar branching coefficients and branching angles using a semi-automated technique. RESULTS: Two hundred and five patients were recruited (104 lacunar stroke, 101 cortical stroke), mean age 68-years (standard deviation 12). With multivariate analysis, increased branching coefficient was associated with periventricular white matter hyperintensities (P=0·006) and ischaemic heart disease (P<0·001), and decreased branching coefficient with deep white matter hyperintensities (P=0·003), but not with lacunar stroke subtype (P=0·96). We found no associations with retinal branching angles. CONCLUSIONS: Retinal arteriolar geometry differs between cerebral small vessel phenotypes. Further research is needed to ascertain the clinical significance of these findings.